2018
DOI: 10.1177/0031512518776847
|View full text |Cite
|
Sign up to set email alerts
|

Mood Effects of Blood Flow Restriction Resistance Exercise Among Basketball Players

Abstract: This study compared the acute effects of resistance exercise with and without blood flow restriction (BFR) on basketball players' mood states. A total of 11 male basketball players (M age = 19.9, SD = 2.8 years; M height = 180.8, SD = 7.8 cm; M weight = 71.1, SD = 9.1 kg; M body mass index = 22.1, SD = 1.9 kg/m) were randomly assigned to two experimental conditions: (a) low-load resistance exercise with BFR (LLRE + BFR) and high-load resistance exercise (HLRE) without BFR. We measured mood state with the Brune… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 34 publications
0
28
0
5
Order By: Relevance
“…To assess these effects multiple studies have assessed an individual's rate of perceived exertion (RPE), 19,36,37 overall mood, 38,39 pain levels, 37 and overall levels of discomfort. 40 When investigating effects on RPE, studies have found when initially training with BFR and low load resistance training RPE was increased in most individuals as compared to traditional high load resistance exercise.…”
Section: Psychosocial Factorsmentioning
confidence: 99%
“…To assess these effects multiple studies have assessed an individual's rate of perceived exertion (RPE), 19,36,37 overall mood, 38,39 pain levels, 37 and overall levels of discomfort. 40 When investigating effects on RPE, studies have found when initially training with BFR and low load resistance training RPE was increased in most individuals as compared to traditional high load resistance exercise.…”
Section: Psychosocial Factorsmentioning
confidence: 99%
“…A couple of studies by Silva et al. [ 18 , 20 ] reported the negative effects of BFR on changes in mood statuses induced by resistance and aerobic exercises. One of their studies found, using low-intensity resistance exercise, that BFR induced negative responses of some mood profiles, measured using the Brunel Mood Scale [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 18 , 20 ] reported the negative effects of BFR on changes in mood statuses induced by resistance and aerobic exercises. One of their studies found, using low-intensity resistance exercise, that BFR induced negative responses of some mood profiles, measured using the Brunel Mood Scale [ 18 ]. In another study, they also determined that the Brunel Mood Scale-measured total mood disturbance immediately after low-intensity aerobic exercise was greater with BFR than with NBFR [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations